Predictors of Weight Loss and Weight Gain in Weight Management Patients during the COVID-19 Pandemic - Jennifer L. Kuk; Rebecca A. G. Christensen; Elham Kamran Samani; Sean Wharton (Journal of Obesity)
Objective. To examine the associations between patient struggles, health, and weight management changes during the COVID-19 pandemic. Methods. 585 patients attending a publicly funded clinical weight management program responded to an electronic survey. Results. Over half of the patients reported worsened overall health, mental health, physical activity, or diet during the pandemic. Approximately 30% of patients lost ≥3% of their body weight and 21% gained ≥3% of their body weight between March and July of the pandemic. Reports of social isolation was associated with increased odds for weight loss in women (OR = 2.0, 1.2–3.3), while low motivation (OR = 1.9, 1.0–3.7), depression (OR = 2.5, 1.0–6.3), and struggles with carbohydrate intake (OR = 2.1, 1.0–4.3) were associated with weight gain. Cooking more at home/eating less take out was associated with increased likelihood of weight loss (OR = 2.1, 1.1–3.9) and lower odds for weight gain (OR = 0.2, 0.1 to 0.97). Working from home was not associated with weight loss or weight gain (P>0.6). Conclusion. The COVID-19 pandemic is associated with certain factors that may facilitate weight loss and other factors that promote weight gain. Thus, depending on the patient experience during the pandemic, prevention of weight gain may be more appropriate than weight loss.